Model-Based Safety and Assessment : 5th International Symposium, IMBSA 2017, Trento, Italy, September 11-13, 2017, Proceedings /: 5th International Symposium, IMBSA 2017, Trento, Italy, September 11-13, 2017, Proceedings. (2017) - Unknown
No abstract available